ANALISIS AKUNTANSI PERSEDIAAN BARANG DAGANGAN PADA PT. RIAU BAN PEKANBARU - Septiana, Emhar; Armas, Riadi; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study was to determine whether the application of accounting for inventories at PT. Riau Ban Pekanbaru in accordance with Statement of Financial Accounting Standards No.14 on Inventory. There are some problems encountered in this study include: accounting treatment of the cost of loading and unloading of goods, PT.Riau Ban does not include costs such as adders unloading acquisition value of inventories and the treatment of proprietary inventory, PT.Riau Ban not acknowledge supplies on the way so that it is not in accordance with Statement of Financial Accounting Standards No.14. For the problem, the authors obtained data related form of primary data in the form of interviews and secondary data, such invoice, purchase reports, card stock, balance sheet, and income statement. The data that has been obtained is analyzed using descriptive methods. The result showed that the application of inventory accounting applied by PT.Riau Ban tires not in accrdance with the Statement of Financial Accaounting Standards No.14.Keywords: Inventory Accounting